2019
DOI: 10.1016/j.artd.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

YouTube is a poor source of patient information for knee arthroplasty and knee osteoarthritis

Abstract: Background The objective of this study was to assess the educational quality of YouTube videos pertaining to total knee arthroplasty and knee osteoarthritis. Methods A systematic search for the terms “knee replacement” and “knee arthritis” was performed using YouTube's search function. Data from the 60 most relevant videos were collected for each search term. Quality assessment checklists with a scale of 0 to 10 points were developed to evaluate the video content. Video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 13 publications
6
35
0
Order By: Relevance
“…Professional societies and Media had highest C-DQS and GQS compared to other sources seem to be spreading quality information on this topic. Multiple studies with similar pretext have been done for various medical conditions, and in agreement, to those, our study also shows that YouTube is a poor and unreliable source of medical information [1,7,[12][13][14][15][16][17][18][19][20][21][22]26]. The Videos from professional societies, the most common video source in our study, received both the highest mean GQS score and C-DQS score.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Professional societies and Media had highest C-DQS and GQS compared to other sources seem to be spreading quality information on this topic. Multiple studies with similar pretext have been done for various medical conditions, and in agreement, to those, our study also shows that YouTube is a poor and unreliable source of medical information [1,7,[12][13][14][15][16][17][18][19][20][21][22]26]. The Videos from professional societies, the most common video source in our study, received both the highest mean GQS score and C-DQS score.…”
Section: Discussionsupporting
confidence: 89%
“…Colorectal cancer (CRC) is the third most common cancer and the second leading cause of cancer-related deaths among men and women in the United States [1]. Colonoscopy is one of the most effective screening methods to prevent CRC [2].…”
Section: Introductionmentioning
confidence: 99%
“…11 YouTube has become an increasingly analyzed source of medical information available on the internet with a variety of recent studies in the literature. 14,[18][19][20][21][22] However, by evaluating videos according to five criteria that the authors felt constituted basic surgical procedure information that a patient should be aware of, this study has shown that the content of the videos available on YouTube regarding fetal surgery for NTDs is insufficient for patient education.…”
Section: Discussionmentioning
confidence: 90%
“…The previous studies have explored the usefulness of YouTube videos in different fields of specialization and found various levels of educational quality. [16][17][18][19][20][21] The current literature lacks information about the usefulness of the YouTube videos for SMBG.…”
mentioning
confidence: 99%